Bailing Out the People? : When Private Debt Becomes Public - Mbaye, Samba (IMF Working Papers; Working Paper, 2018)
This paper documents a form of private sector bailout that is much more common (and yet unnoticed) than the typical bank bailout. Building on the newly-created Global Debt Database, we show that excess private debt systematically turns into higher public debt, regardless of whether the credit boom resulted in a crisis or a more orderly deleveraging process. This debt migration operates mainly through growth rather than explicit bailouts: private deleveraging weighs on activity, prompting a countercyclical government response to support economic activity. Ultimately, whether this debt substitution results in a net increase or a net decline of overall indebtedness in the economy depends on the extent of the growth slowdown during the deleveraging spell. These findings suggest that markets and policymakers should move away from looking at private and sovereign debt in silos and pay closer attention to the total stock of debt in the economy, as the line between the two tends to become blurry.